The interference of anti-TSH autoantibody on clinical TSH detection - Tang, Mulin; Meng, Xue; Ni, Jiajia; Liu, Xue; Wang, Xinhui; Li, Yuchen; Chai, Yuwei; Kou, Chunjia; Zhang, Li; Zhang, Haiqing (Frontiers in Endocrinology, 2024)
Objective It is well known that macro-thyroid-stimulating hormone (macro-TSH) could interfere with the detection of TSH. The anti-TSH autoantibody is an essential component of macro-TSH. However, the epidemiological characteristics and the clinical interference of the anti-TSH autoantibody are unclear. Methods In this study, the radioimmunoprecipitation technique was used to detect the anti-TSH autoantibody. Platforms with different detection mechanisms were applied to measure the TSH in patients with the anti-TSH autoantibody. Polyethylene glycol (PEG) precipitation was used to determine the immunoassay interference. Results The prevalence of the anti-TSH autoantibody in patients with mild subclinical hypothyroidism (SCH) and autoimmune thyroiditis, but normal thyroid function, was 4.78%. All 10 patients with anti-TSH antibodies had autoimmune diseases, with five of them having significant clinical test interference. Conclusion The appearance of the anti-TSH antibody is not associated with thyroid autoantibodies. The presence of the anti-TSH autoantibody can interfere with the detection of TSH and can affect clinical diagnosis and treatment.